The Influence of Online Motivation and Presence on the Performance of State Vocational School Teachers in Tangerang District During the Covid-19 Pandemic - Mansur, Mansur; Sri Setya Handayani (Dinasti International Journal of Digital Business Management, 2023)
The Effect of Motivation and Online Presence on the Performance of State Vocational School Teachers in Tangerang Regency during the Covid 19 Pandemic. Based on observations of the performance of State Vocational School teachers in Tangerang Regency, it shows that motivation has decreased and low attendance. Information from school operators as teacher attendance record officers, that there are 40% of teachers who are late for teaching every month. Apart from that, from conversations with some of the closest teachers, the attendance recording system and low motivation caused teachers to lack enthusiasm in carrying out their activities. The aim is to find out to what extent motivation and online attendance have an effect on improving teacher performance. The population in this study was taken from State Vocational School teachers in Tangerang Regency. The research was conducted from January to June 2021. This research used a quantitative descriptive approach by collecting data using a questionnaire which was distributed to sample schools through social media networks in the form of groups. whatsapp specifically for teachers with a total of 238 teachers. The analytical method uses multiple linear regression analysis with the help of the SPSS program. The results showed that the motivational variable had no effect on the teacher's performance variable, but the online attendance variable had a significant effect on the teacher's performance variable. Simultaneously, the two independent variables show that motivation and online presence have an effect on increasing teacher performance at State Vocational Schools in Tangerang Regency during the Covid 19 Pandemic.